Analisis Filogenetik Gen Hemaglutinin dan Neuraminidase Avian Influenza H9N2 Asal Ayam Petelur di Jawa Timur (PHYLOGENETIC ANALYSIS OF HAEMMAGLUTININ AND NEURAMINIDASE GENES OF AVIAN INFLUENZA H9N2 FROM LAYER INI EAST JAVA) - Rachmawati, Prestalia Dwi; Adikara, Tatang Santanu; Plumeriastuti, Hani; Ernawati, Rahaju; Rahmahani, Jola; Handijatno, Didik; Nugroho, Christian Marco Hadi (Jurnal Veteriner; Vol 21 No 2 (2020), 2020)
Avian influenza virus (AIV) subtype H9N2 is one of the infectious agents that threatens laying poultry farms, because it has an impact on drastically reducing production in the population. The aim of this study was to isolate and analyze phylogenetically the partial gene encoding the surface proteins of the AIV subtype H9N2 from laying hens in East Java.  A total of 30 suspected AIV subtypes of H9N2 were taken from laying hens which had decreased production by up to 70% in three sub districts each in Kediri, Blitar and Tulung Agung regency, in East Java Province. The virus was isolated in embryonated chicken eggs and then followed by a Hemagglutination (HA) test.  Detection of the presence of H9 and N2 genes was carried out through Reverse Transcriptase polymerase Chain Reaction (RT-PCR) and continued with partial gene sequencing of the two surface proteins.  Data analysis was processed using BioEdit version 7.2.5 and Mega 7.0. The results show that only one sample, namely code B2.2 from Blitar regency, is an AIV subtype of H9N2. The virus in this study belong to clade h9.4.2.5 of the AIV subtype H9N2. The conclusion of this study is that the VAI subtype H9N2 was successfully isolated from laying hens in East Java and successfully identified phylogenetically.